Ethnography Study: How to Manage Financial Condition in the Capital/Urban City DKI Jakarta Situation Among Minangkabau Ethnis, West Sumatera - Alam, Taris Zakira; Heikal, Jerry (Universitas Pahlawan Tuanku Tambusai, 2024)
The Minang tribe is one of the tribes in Indonesia that have ‘migrated customs’ (merantau). The word ‘merantau’ itself is a manifestation of leaving the original territory and occupying other new territory. Individuals Minangkabau and businesses have had to adapt to the situation when they moved to the capital/urban city and has required to manage their financial strategies to weather the storm. This study is to understand how to manage financial condition in the capital/urban city DKI Jakarta situation among Minangkabau Ethnis, West Sumatra. This research is a qualitative research using Ethnography Method. Data collection was carried out by In-depth interviews, life-histories, and documentary data. From the results of this study, it can be concluded that there are difference personal statement between the subject relate to social norms and preferences to select the financial management and business that would like to get into. For the shared values/points, there are three shared values/points from the subjects in how to manage financial condition in in the capital city among from Minangkabau ethnis. There are a need to set clear financial goals; If required additional fund: try finding sources of funds, monitoring budget compare with implementation, flexible and keep updating with the current situation, and comprehensively understanding the plan by keeping open mind to be updated the relevant factors, investment strategy for the future, and how to face the difficult situation in the capital city. The research uses a survey via interview developed by Taris Zakira Alam (2023). Participants were asked 11 questions about their financial conditions before “Merantau” and after “Merantau”, financial behavior, financial planning, about their self-efficacy related to money, self-efficacy refers to a feeling of being able to deal effectively with a situation, investment target and planning. Those questions were included because self-efficacy issues are critical factors in determining whether people believe they are capable of making changes in the financial behavior and knowledge areas that are being measured in the evaluation process.